Cybersecurity governance in the healthcare sector during digital transformation: an integrated model and hybrid analytical approach - Alharbi, Amnah; Alkhalifah, Ali (Frontiers in Public Health, 2025)
IntroductionDigital transformation is increasingly relied upon in the healthcare sector, enhancing service efficiency but posing security challenges related to privacy and trust. With the increasing use of digital technologies, cybersecurity issues are becoming more critical, especially given the risks of breaches and data leaks. Therefore, understanding the impact of security factors on employee security behavior during digital transformation is critical.MethodsBased on general deterrence theory and protection motivation theory, this study developed a research framework for examining digital transformation factors, such as complexity (the interconnectedness of diverse digital health systems) and exploitability (the potential for vulnerabilities in those systems to be leveraged by attackers), and cybersecurity-related factors, such as privacy, trust, and awareness, and to understand how they influence employee behavior in healthcare. Data were collected from 252 healthcare workers in Saudi Arabia and analyzed using structural equation modeling and artificial neural networks.ResultsThe results showed that trust, exploitability, awareness, and certainty of punishment significantly impact security behavior during digital transformation. Privacy concerns and complexity were also found to significantly influence threat assessment and response evaluation. However, consistent with some studies in managed security environments, perceived vulnerability, perceived threat, and self-efficacy had no impact on security behavior. Finally, the study presents its theoretical and applied contributions and recommendations for future research.